Systematic Analysis of Tobacco CrRLK1L Family Genes and Functional Identification of NtCrRLK1L47 in Environmental Stresses - Li, Xiaoxu; Guo, Cun; Wang, Qi; Li, Zhiyuan; Cai, Jun; Wu, Dousheng; Li, Yangyang; Yang, Aiguo; Guo, Yongfeng; Gao, Junping; Wen, Liuying; Pu, Wenxuan (Frontiers in Plant Science, 2022)
The Catharanthus roseus RLK1-like (CrRLK1L) family is involved in the regulation of plant reproduction, growth and development, cell wall integrity sensing as well as responses to both biotic and abiotic stress conditions. The extraordinary progress has been made in elucidating CrRLK1L family receptor kinases-mediated signaling pathway, while, limited research addressed the functions of CrRLK1L proteins in tobacco. In current study, we identified and analyzed 48 NtCrRLK1L members from the tobacco genome. The newly identified NtCrRLK1L members were divided into seven groups together with the Arabidopsis CrRLK1L members. The syntenic analysis revealed that four pairs of NtCrRLK1L genes were predicted to have arisen from segmental duplication events. Expression profiling showed that the NtCrRLK1L genes were expressed in various tissues, and most NtCrRLK1L genes were induced by salt and drought stress conditions. Notably, NtCrRLK1L47 was up-regulated under drought and salinity stresses and the NtCrRLK1L47-GFP fusion protein was located in the cell membrane. Further, overexpression of NtCrRLK1L47 gene could enhance the salt tolerance in tobacco seedlings.